PERCENTAGE ANALYSIS OF BOQ FORMING COMPONENTS FOR THE RELOCATION HOUSE IN KETAPANG VILLAGE - Irfanto, Ryobi; Manulye, Ian Hendrata; Lidyawati, Rut (Universitas Trisakti, 2023)
The Cost Budget Plan (CBP) is the main aspect of project implementation in calculating the estimated overall costs required to establish a construction project. This research aims to determine the percentage value of the work components that form the Cost Budget Plan (CBP) and determine the implementation budget or actual costs incurred for each job. The research was carried out in urban slum areas, one of the locations reviewed was Ketapang Village, which is located in Mauk District, Tangerang Regency, Banten Province. Ketapang Village. Data collection in this research used calculations of working drawing volumes based on unit prices from Banten Gubernatorial Regulation No. 39 of 2021 and implementation volumes using unit prices based on surveys by the Community Self-Reliance Agency. In processing the CBP data, the overall CBP recapitulation calculation results were IDR 81,001,345. The largest cost of components forming the CBP occurred in architectural work amounting to IDR 36,213,105 with a percentage value of 44.71%. The wage component which has a percentage of 14.81% shows that the material component that makes up a simple house is 85.19%.